Penggunaan Modul Elektronik Berbasis Isu Sosiosaintifik untuk Meningkatkan Persepsi Siswa tentang Bioteknologi - Fitri Husni Mardiyah; Widi Purwianingsih; Rini Solihat (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Currently, the world has faced a new normal era, many schools have started to conduct limited face-to-face learning. But unfortunately, student learning hours at school are very limited. Students are required to be able to study independently outside of school hours. The module is one of the learning tools that can be accessed anywhere without being bound by time. On the other hand, at this time technology is developing rapidly, one of which is technology in the field of biology or can be called biotechnology. The development of biotechnology has an impact on life. Many people do not have a good perception of biotechnology. There needs to be an increase in community competence, one of which is through the field of education or specifically is that students can have a good perception based on scientific decisions through socio-scientific issues. This study aims to analyze the effectiveness of using electronic modules based on socioscientific issues in increasing students' perceptions of biotechnology. This study uses a quasi-experimental design method. The research design used was a non-equivalent control group design. The sample in this study was grade 12 students consisting of 120 students who were determined by purposive sampling technique. The results of this study indicate that there are significant differences in students' perceptions of biotechnology after using the module. The Mann Whitney test on the value of students' perceptions of biotechnology shows a number (2-tailed = 0.003) < (0.05) which means that learning using electronic modules based on socioscientific issues has an influence on students' perceptions of biotechnology.